2013
DOI: 10.1242/dev.088799
|View full text |Cite
|
Sign up to set email alerts
|

The Abelson tyrosine kinase regulates Notch endocytosis and signaling to maintain neuronal cell fate inDrosophilaphotoreceptors

Abstract: SUMMARYThe development of a functional organ requires coordinated programs of cell fate specification, terminal differentiation and morphogenesis. Whereas signaling mechanisms that specify individual cell fates are well documented, little is known about the pathways and molecules that maintain these fates stably as normal development proceeds or how their dysregulation may contribute to altered cell states in diseases such as cancer. In Drosophila, the tyrosine kinase Abelson (Abl) interfaces with multiple sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
5
14
0
Order By: Relevance
“…1I, K). This inconsistency might be ascribed to some factors induced by hypoxia that are involved in hypoxia-induced neurogenesis such as Notch 1 signaling [33][34][35]. Notch 1 is known to be crucial for the self-renewal and fate-decision of NSCs and promotes ischemia-induced neurogenesis in the hippocampus by cleaving Notch 1 and increasing the level of NICD (notch intracellular domain), the active form of Notch 1 that translocates to the nucleus and regulates transcription [36,37].…”
Section: Pfk-1 Reduces the Neuronal Differentiation Of Nscs After Hypmentioning
confidence: 99%
“…1I, K). This inconsistency might be ascribed to some factors induced by hypoxia that are involved in hypoxia-induced neurogenesis such as Notch 1 signaling [33][34][35]. Notch 1 is known to be crucial for the self-renewal and fate-decision of NSCs and promotes ischemia-induced neurogenesis in the hippocampus by cleaving Notch 1 and increasing the level of NICD (notch intracellular domain), the active form of Notch 1 that translocates to the nucleus and regulates transcription [36,37].…”
Section: Pfk-1 Reduces the Neuronal Differentiation Of Nscs After Hypmentioning
confidence: 99%
“…The results of the present study indicated that Past1 plays a role during eye development, which is known to be regulated by Notch [17, 19, 27, 40]. Interestingly, endocytosis of Notch seemed abnormal in early-mid pupal mutant eyes.…”
Section: Discussionmentioning
confidence: 61%
“…We examined Sce mutant R7s throughout larval and pupal development and found none that misexpressed Svp, nor did we observe Sce or Scm mutant R7s that displayed other R1/R6 characteristics, such as large rhabdomeres positioned at the periphery of the ommatidium or expression of the R1-R6-specific rhodopsin Rh1; [ 28 , 29 , 45 ]). While loss of the Abelson kinase was recently shown to cause R neurons to lose expression of the neuronal marker Elav and switch to a non-neuronal pigment cell fate [ 50 ], we found that Sce and Scm mutant R1/R6s and R7s maintain expression of Elav and the photoreceptor-specific protein Chaoptin (for example, Figure 1 B), indicating that their commitment to a neuronal fate is also independent of PcG gene function. We conclude that R7s use Sce and Scm to maintain repression of one but not all alternative binary fate choices.…”
Section: Discussionmentioning
confidence: 47%